2023
DOI: 10.1021/acssensors.2c02614
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Multiparametric Approach To Determine Sweat–Blood Lactate Bioequivalence

Abstract: Many sweat-based wearable monitoring systems have been recently proposed, but the data provided by those systems often lack a reliable and meaningful relation to standardized blood values. One clear example is lactate, a relevant biomarker for both sports and health sectors, with a complex sweat−blood bioequivalence. This limitation decreases its individual significance as a sweat-based biomarker. Taking into account the insights of previous studies, a multiparametric methodology has been proposed to predict b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To know the relationship between the lactate levels in blood and sweat, a bioequivalence study was carried out by the authors of this work. The study is described in [32], which concludes that there is no direct equivalence between blood lactate and sweat lactate without considering other parameters. To estimate the equivalence, a custom algorithm that takes HR, perspiration level, and sweat lactate concentration as inputs is required.…”
Section: Cartridgementioning
confidence: 99%
“…To know the relationship between the lactate levels in blood and sweat, a bioequivalence study was carried out by the authors of this work. The study is described in [32], which concludes that there is no direct equivalence between blood lactate and sweat lactate without considering other parameters. To estimate the equivalence, a custom algorithm that takes HR, perspiration level, and sweat lactate concentration as inputs is required.…”
Section: Cartridgementioning
confidence: 99%
“…While many studies have observed a high correlation between blood and sweat metabolites ( Xuan et al, 2023b ; Rabost-Garcia et al, 2023 ), others have claimed no such correlation ( Lamont, 1987 ). However, the studies that reported no correlation had small sample sizes, employed non-standard methods of sample collection and analysis, did not distinguish between active and latent muscles, and had imprecise research designs ( Karpova et al, 2020 ).…”
Section: Relationship Between Blood Lactate and Sweat Lactatementioning
confidence: 99%
“…Nevertheless, the lack of consistency in the ratios of biomarkers in sweat and blood in many studies might be due to relatively scant data ( Xuan et al, 2023b ). However, the clear difference in metabolite amounts in sweat (5–40 mmol/L) and blood (0.5–25 mmol/L) ( Baker and Wolfe, 2020 ) suggests that correlation and regression analyses specific to the situation and environment are needed ( Rabost-Garcia et al, 2023 ). Moreover, given the differences in metabolite concentrations based on the site of sweat collection, further research is needed to examine concentrations depending on the type of exercise and placement of the wearable device on the body.…”
Section: Relationship Between Blood Lactate and Sweat Lactatementioning
confidence: 99%
See 1 more Smart Citation
“…The use of electronic devices for monitoring sports skills has made it possible to meet people's requirements for the accuracy and safety of spontaneous physical exercise. This technology has been widely adopted and has obtained positive impacts on promoting human health [15][16][17].…”
Section: Introductionmentioning
confidence: 99%